2007
DOI: 10.1080/00029157.2007.10401611
|View full text |Cite
|
Sign up to set email alerts
|

Selective Biasing of a Specific Bistable-Figure Percept Involves fMRI Signal Changes in Frontostriatal Circuits: A Step Toward Unlocking the Neural Correlates of Top-Down Control and Self-Regulation

Abstract: Attention, suggestion, context and expectation can all exert top-down influence on bottom-up processes (e.g., stimulus-driven mechanisms). Identifying the functional neuroanatomy that subserves top-down influences on sensory information processing can unlock the neural substrates of how suggestion can modulate behavior. Using functional magnetic resonance imaging (fMRI), we scanned 10 healthy participants (five men) viewing five bistable figures. Participants received a directional cue to perceive a particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 90 publications
(91 reference statements)
2
19
0
Order By: Relevance
“…Other depth studies used methods more similar to those used for binocular rivalry, such as multivoxel pattern analysis [8], event-related adaptation [15], event-related designs in which brain activation was correlated to changes in perceived depth [5,16], or adaptation in a block design to assess population responsiveness to different types of depth stimuli [14]. These differences in methodology also mean that subjects performed a task in rivalry or multistabiity studies using event-related designs [5,19,20,22,[28][29][30]32,33,36], or block designs [1,2,26,31,34,35], but subjects did not perform tasks in depth studies [3,6,[9][10][11][12][13]17], although there are a few exceptions to this generalization for depth [2,4,5,7,17]. Also, a few rivalry or multistability studies did not use a task [21,37,61], and some rivalry studies used fixation tasks unrelated to the perception of rivalry [23,28].…”
Section: Methodological Issues In Fmri Studies and Role Of Frontal Areasmentioning
confidence: 99%
See 4 more Smart Citations
“…Other depth studies used methods more similar to those used for binocular rivalry, such as multivoxel pattern analysis [8], event-related adaptation [15], event-related designs in which brain activation was correlated to changes in perceived depth [5,16], or adaptation in a block design to assess population responsiveness to different types of depth stimuli [14]. These differences in methodology also mean that subjects performed a task in rivalry or multistabiity studies using event-related designs [5,19,20,22,[28][29][30]32,33,36], or block designs [1,2,26,31,34,35], but subjects did not perform tasks in depth studies [3,6,[9][10][11][12][13]17], although there are a few exceptions to this generalization for depth [2,4,5,7,17]. Also, a few rivalry or multistability studies did not use a task [21,37,61], and some rivalry studies used fixation tasks unrelated to the perception of rivalry [23,28].…”
Section: Methodological Issues In Fmri Studies and Role Of Frontal Areasmentioning
confidence: 99%
“…These frontal and parietal areas were the most frequently reported sites of activation in these studies. However, several studies confirmed that activation also occurs in occipital areas, including ventral occipital (fusiform gyrus) [1,29,32,36], medial temporal areas (hMT+) [19,30,32,33,[35][36][37][38] and areas V1, V2, V3, V3A or V4-d topo [1,5,31,32,37,38].…”
Section: Multistabilitymentioning
confidence: 99%
See 3 more Smart Citations